Modern Slavery: Understanding Human Trafficking through the Lens of Surah An-Nur Verse 33 - Ihsanniati, Nurlina Sari; Ramadhan, M Nur Gema; Ilmi, Moh Hudal Hafid; Al-Murod, Siti Aldasari Dwi Rohmawati (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2024)
Human trafficking is one of the most serious crimes still rampant around the world, threatening human rights and individual dignity. An understanding of religious teachings, particularly Islam, can provide an in-depth look into this issue. Surah An-Nur Verse 33 of the Quran becomes the focal point of this study to explore the Islamic perspective on human trafficking. This research aims to analyze the Islamic view on human trafficking through the interpretation of Surah An-Nur Verse 33. The research method used is a qualitative approach. A text analysis of Surah An-Nur Ayat 33 was conducted to identify the moral values and messages contained therein. In addition, a literature study was used to explore the relationship between Islamic views and the actual context of human trafficking. Surah An-Nur Verse 33 asserts that Islam categorically rejects all forms of human slavery and oppression. This verse underscores the importance of preserving human dignity and asserts that the practice of human trafficking goes against the moral principles taught by the Quran. The implication of this understanding is the need for concrete actions in combating human trafficking, including public education efforts and stricter law enforcement. Understanding the Islamic perspective, especially through Surah An-Nur Verse 33, provides a strong moral foundation for the protection of human trafficking victims and the eradication of this criminal practice.